Peningkatan Kualitas Pengelolaan Kantin Universitas berbasis Sistem Jaminan Produk Halal: Implementasi Kebijakan Wajib Halal di Indonesia - Sandika, Bayu; Dewi, Rosita Fitrah (JPM: Jurnal Pengabdian Masyarakat, 2026)
Regulations have been issued in the Instruction of the Minister of Religious Affairs Number 1 of 2023 concerning Halal Certification of Products and Canteens in Work Units under the Ministry of Religious Affairs, which mandates that canteens in the work units of the Ministry of Religious Affairs are expected to have halal certification, including on Islamic university However, field data shows that there are six canteens on the UIN KHAS Jember that do not yet have halal certification. This community service activity aims to improve the quality and management of canteens based on the Halal Product Assurance System on the UIN KHAS Jember. This community service activity was carried out using the Non-participatory Action Research model, which includes several stages, namely 1) identification, 2) design, 3) approval, 4) implementation, 5) completion, 6) operation, and 7) evaluation. The results show that there are three UIN KHAS Jember canteens that are ready to apply for halal certificates. The canteens that are declared ready have complete legal formalities that meet the requirements, so they are considered ready to continue to apply for halal certificates. Based on the description, it can be concluded that to improve the quality of canteen management on the UIN KHAS Jember, it is necessary to improve the quality of canteen management, mentoring canteens to move up a class, halal socialization, mentoring in preparing Halal Product Assurance System, and mentoring in submitting halal certificates. Abstracts must not contain tables/figures and do not include citations. It is not permitted to use abbreviations except for units of a quantity and use them to a minimum.